Natural plasmid transformation in a high-frequency-of-transformation marine Vibrio strain. - Frischer, M E (1990)
The estuarine bacterium Vibrio strain DI-9 has been shown to be naturally transformable with both broad host range plasmid multimers and homologous chromosomal DNA at average frequencies of 3.5 X 10(-9) and 3.4 X 10(-7) transformants per recipient, respectively. Growth of plasmid transformants in nonselective medium resulted in cured strains that transformed 6 to 42, 857 times more frequently than the parental strain, depending on the type of transforming DNA. These high-frequency-of-transformation (HfT) strains were transformed at frequencies ranging from 1.1 X 10(-8) to 1.3 X 10(-4) transformants per recipient with plasmid DNA and at an average frequency of 8.3 X 10(-5) transformants per recipient with homologous chromosomal DNA. The highest transformation frequencies were observed by using multimers of an R1162 derivative carrying the transposon Tn5 (pQSR50). Probing of total DNA preparations from one of the cured strains demonstrated that no plasmid DNA remained in the cured strains which may have provided homology to the transforming DNA. All transformants and cured strains could be differentiated from the parental strains by colony morphology. DNA binding studies indicated that late-log-phase HfT strains bound [3H]bacteriophage lambda DNA 2.1 times more rapidly than the parental strain. These results suggest that the original plasmid transformation event of strain DI-9 was the result of uptake and expression of plasmid DNA by a competent mutant (HfT strain). Additionally, it was found that a strain of Vibrio parahaemolyticus, USFS 3420, could be naturally transformed with plasmid DNA. Natural plasmid transformation by high-transforming mutants may be a means of plasmid acquisition by natural aquatic bacterial populations.